RESILIENSI STRUKTUR KELUARGA NELAYAN: STUDI KASUS RESPON KELUARGA NELAYAN TERHADAP DAMPAK PERUBAHAN IKLIM DI PANTAI PASAR BAWAH BENGKULU SELATAN - Hasibuan, Febrina; Widiono, Septri; Badruddin, Redy (Jurnal AGRISEP, 2017)
A study in addresing the resilience of the family structure of fishermen to the impacts of climate change was necessary in the context survival strategy of fishermen family. This research was conducted in the beach of Pasar Bawah, Pasar Manna South Bengkulu by using the case study strategy. Primary data was collected by in-deepth interviewing some key informant and participant observation some specific location.The research found that the impact of climate change experienced by fishermen were a tidal wave, a change in wind direction, extreme weather, the shifting seasons and shifting fishing area. The vulnerability of fishermen community were seen from the level of exposure, the sensitivity and adaptability. This vulnerability affected the family structure of fishermen so that they have to take action in order to survive and able to achieve resilience family. But the impact of climate change did not affected the family structure became disturb. The structure of family such as differentiation of roles, allocation of economic, political allocation, allocation allocation solidarity and integration were functional.